Folate and Cobalamin Modify Associations between S-adenosylmethionine and Methylated Arsenic Metabolites in Arsenic-Exposed Bangladeshi Adults. Issue 5 (5th March 2014) - Howe, Caitlin G.; Niedzwiecki, Megan M.; Hall, Megan N.; Liu, Xinhua; Ilievski, Vesna; Slavkovich, Vesna; Alam, Shafiul; Siddique, Abu B.; Graziano, Joseph H.; Gamble, Mary V.
Abstract: Chronic exposure to inorganic arsenic (InAs) through drinking water is a major problem worldwide. InAs undergoes hepatic methylation to form mono- and dimethyl arsenical species (MMA and DMA, respectively), facilitating arsenic elimination. Both reactions are catalyzed by arsenic (+3 oxidation state) methyltransferase (AS3MT) using S -adenosylmethionine (SAM) as the methyl donor, yielding the methylated product and S -adenosylhomocysteine (SAH), a potent product-inhibitor of AS3MT. SAM biosynthesis depends on folate- and cobalamin-dependent one-carbon metabolism. With the use of samples from 353 participants in the Folate and Oxidative Stress Study, our objective was to test the hypotheses that blood SAM and SAH concentrations are associated with arsenic methylation and that these associations differ by folate and cobalamin nutritional status. Blood SAM and SAH were measured by HPLC. Arsenic metabolites in blood and urine were measured by HPLC coupled to dynamic reaction cell inductively coupled plasma MS. In linear regression analyses, SAH was not associated with any of the arsenic metabolites. However, log(SAM) was negatively associated with log(% urinary InAs) (β: −0.11; 95% CI: −0.19, −0.02; P = 0.01), and folate and cobalamin nutritional status significantly modified associations between SAM and percentage of blood MMA (%bMMA) and percentage of blood DMA (%bDMA) ( P = 0.02 and P = 0.01, respectively). In folate- and cobalamin-deficient individuals, log(SAM) was positively associated with %bMMA (β: 6.96; 95% CI: 1.86, 12.05; P < 0.01) and negatively associated with %bDMA (β: −6.19; 95% CI: −12.71, 0.32; P = 0.06). These findings suggest that when exposure to InAs is high, and methyl groups are limiting, SAM is used primarily for MMA synthesis rather than for DMA synthesis, contributing additional evidence that nutritional status may explain some of the interindividual differences in arsenic metabolism and, consequently, susceptibility to arsenic toxicity.